PENGARUH PENDIDIKAN KESEHATAN MASALAH KESEHATAN REPRODUKSI TERHADAP SIKAP MENJAGA KESEHATAN REPRODUKSI PADA SISWI KELAS II MULTIMEDIA DI SMK KRIYA SAHID SUKOHARJO - -, Endang Dwi Ningsih; -, Ratna Indriati (Politeknik Insan Husada Surakarta, 2015)
Background: One of the factors that influence the of reproduction health issues is the lack of knowledge about reproductive health knowledge. Related to this the researchers interested in studying about the influence of educating reproduction health to the the reproductive health maintain attitude toward the female students in class II Multimedia of SMK Kriya Sahid Sukoharjo.Objective: This study was to determine the influence of educating reproduction health to the reproductive health maintain attitude toward the female students in class II Multimedia of SMK Kriya Sahid Sukoharjo.Method: Used the study design with pre experimental design with the approaching method is one group pretest postest design. The subjects were 30 class II Multimedia students of SMK Kriya Sahid Sukoharjo. The datas collected and analyzed by Paired t test with α 0,05.Results: The datas analyzed by Paired t test, SPSS version 18 with α = 5% ( 0,05). The cunted t = - 9,560, p value is 0,000< 0,05. It mean Ha accepted and Ho rejected. Conclusion is the educating reproduction health has significant influence to the reproduction health maintain attitude of the female students class II Multimedia of SMK Kriya Sahid SukoharjoKeywords: Health Educating, Reproduction Health, Attitude in keeping Reproduction Health.